2022
DOI: 10.1021/jacs.2c09004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Analysis of the Biosynthesis of the Aspartimidylated Graspetide Amycolimiditide

Abstract: Several classes of ribosomally synthesized and post-translationally modified peptides (RiPPs) are composed of multiple macrocycles. The enzymes that assemble these macrocycles must surmount the challenge of installing a single specific set of linkages out of dozens of distinct possibilities. One class of RiPPs that includes multiple macrocycles are the graspetides, named after the ATP-grasp enzymes that install ester or amide linkages between pairs of nucleophilic and electrophilic side chains. Here, using het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 40 publications
(108 reference statements)
2
37
0
Order By: Relevance
“…As introduced above, the hydrolysis of lihuanodin is regioselective to give Asp and no isoAsp (Figure c). This is in stark contrast to the hydrolysis of aspartimides formed by canonical PIMTs as well as in fuscimiditide, amycolimiditide, and OlvA­(BCS A ), which are regioselective favoring isoAsp. , We further confirmed this result by treating hydrolyzed lihuanodin with human PIMT, which will convert isoAsp (and not Asp) to aspartimide, , and observed no reaction (Figure a). As we showed previously, the hydrolyzed material is quantitatively converted to lihuanodin upon LihM treatment.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…As introduced above, the hydrolysis of lihuanodin is regioselective to give Asp and no isoAsp (Figure c). This is in stark contrast to the hydrolysis of aspartimides formed by canonical PIMTs as well as in fuscimiditide, amycolimiditide, and OlvA­(BCS A ), which are regioselective favoring isoAsp. , We further confirmed this result by treating hydrolyzed lihuanodin with human PIMT, which will convert isoAsp (and not Asp) to aspartimide, , and observed no reaction (Figure a). As we showed previously, the hydrolyzed material is quantitatively converted to lihuanodin upon LihM treatment.…”
mentioning
confidence: 57%
“…Protein isoaspartyl methyltransferases (PIMTs) make up a family of enzymes that reverse damage in aging proteins. PIMTs restore function of proteins that have accumulated isoaspartyl residues by driving their conversion to the l -aspartyl form . PIMTs are highly conserved and are found in almost all eukaryotic cells and Gram-negative bacteria. , In Gram-positive bacterial genomes, recent work by our group as well as van der Donk and co-workers has illustrated that enzymes homologous to PIMTs are associated with several ribosomally synthesized and post-translationally modified peptide (RiPP) biosynthetic gene clusters (BGCs), , specifically in the BGCs of lasso peptides cellulonodin-2 and lihuanodin (Figure a,b), graspetides fuscimiditide and amycolimiditide, , and lanthipeptide OlvA­(BCS A ) . The PIMT homologues in cellulonodin-2 and lihuanodin BGCs, TceM and LihM, respectively, recognize matured lasso peptides pre-cellulonodin-2 and pre-lihuanodin as substrates , and methylate the first aspartate residue in a conserved DTAD motif in the lasso peptide ring, using S -adenosylmethionine (SAM) (Figure c) .…”
mentioning
confidence: 99%
“…We named this putative imiditide mNmaA M following the nomenclature used in our study on amycolimiditide, where m stands for modified, and superscripted M stands for the methyltransferase. 21 Our observation indicated that the rate of methylation was faster than the rate of aspartimidylation for the biosynthesis of mNmaA M (Figure S6). Since NmaM is homologous to PIMT, we wonder whether Pcm, the housekeeping PIMT in E. coli, could alter the intended product in vivo.…”
Section: Heterologous Expression Of Imiditide From Nonomuraea Maritimamentioning
confidence: 71%
“…Both amycolimiditide and pre-amycolimiditide have 4 ester linkages, but amycolimiditide has an additional aspartimide moiety suggested by the solution NMR structure (PDB: 8DYM). 21 Indeed, both spectra showed a peak at 1742 cm -1 , indicating the presence of esters. Additionally, the FTIR spectrum for amycolimiditide also contains an additional peak at 1708 cm -1 , indicating this peak corresponds to an aspartimide formation (Figure S12).…”
Section: Mnmaa M Contains An Aspartimide Moietymentioning
confidence: 94%
See 1 more Smart Citation